2014
DOI: 10.1097/brs.0000000000000116
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Insertional Torque During Pedicle Screwing Using Cortical Bone Trajectory Technique

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 25 publications
2
180
0
4
Order By: Relevance
“…22 It has also been reported, in terms of mechanical behavior in vivo, that the insertional torque of pedicle screws using the CBT technique was 71% higher than that of the TT technique. 19 Even though the superior stability of axial screw fixation using CBT has been demonstrated, little is known about the biomechanical stiffness of the screw-bone interface against multidirectional loading. Furthermore, there are some concerns about the fixation stability of CBT.…”
Section: 23mentioning
confidence: 99%
See 1 more Smart Citation
“…22 It has also been reported, in terms of mechanical behavior in vivo, that the insertional torque of pedicle screws using the CBT technique was 71% higher than that of the TT technique. 19 Even though the superior stability of axial screw fixation using CBT has been demonstrated, little is known about the biomechanical stiffness of the screw-bone interface against multidirectional loading. Furthermore, there are some concerns about the fixation stability of CBT.…”
Section: 23mentioning
confidence: 99%
“…To achieve a simulation resembling a clinical situation, the TT screw was 6.5 mm in diameter and 40 mm in length, and the CBT screw was 5.5 mm in diameter and 35 mm in length. 19 Each screw was carefully placed in the appropriate position to prevent any cortical breaching and bicortical purchase into the anterior vertebral body because these two conditions may potentially influence screw fixation values.…”
Section: Insertional Trajectorymentioning
confidence: 99%
“…Moreover, only a few studies have reported the biomechanical, clinical, and radiological outcomes in actual surgical cases (3,9). Therefore, the data on this technique are as yet limited.…”
Section: Future Investigationmentioning
confidence: 99%
“…For the right and left CBT screw insertion, the points are at 7 o'clock and 5 o'clock of the pedicle, respectively (Figure 4). This is similar to the technique proposed by Matsukawa et al (3). The lateral view on the image intensifier is used to understand the sagittal trajectory of CBT screwing ( Figure 5).…”
Section: Surgical Techniquementioning
confidence: 99%
“…More practically replicating a mechanism of pedicle screw loosening, Baluch et al compared the fixation strength of CBT screws (average 4.5-mm diameter and 32-mm length) with that of TT screws (average 6.5-mm diameter and 45-mm length) under cyclic loads perpendicular to the screw axis, and demonstrated the superior resistance of CBT screws 23) . Another study also evaluated the mechanical behavior of CBT screws in vivo by measuring insertional torque 24) . The mean maximum insertional torque of CBT screws (5.5-mm diameter and 30-to 35-mm length) was 71% higher than that of TT screws (6.5-to 7.5-mm diameter and 40-mm length).…”
Section: Fixation Strength Of Cbt Screwmentioning
confidence: 99%